Incomplete Kawasaki Disease in a Three Month Old Infant - M, Ashraf; A, Taleb; A, Shamsah; H, Al- Sharhan (Indian Journal of Case Reports, 2020)
Kawasaki disease (KD) is an acute systemic vasculitis of unknown aetiology that has largely replaced rheumatic heart disease as a cause of acquired heart disease in children of many developed countries. We report a case of incomplete KD in a threemonth- old girl. The diagnosis of incomplete KD was made after exclusion of conditions with similar presentation. She was treated with intravenous immunoglobulin following which she made an uneventful recovery but demonstrated thrombocytosis in the second week of convalescence. It is important for the treating physicians to become aware of the incomplete KD as prompt diagnosis and early treatment of these patients with intravenous immunoglobulin is vital for the prevention of lethal coronary complications. Physicians need to have a "high index of suspicion" for KD and even, higher for IKD.